1997
DOI: 10.1096/fasebj.11.6.9194527
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Mel 1a ‐melatonin receptor mRNA in T and B subsets of lymphocytes from rat thymus and spleen

Abstract: In the present work we analyze by reverse transcription, polymerase chain reaction, cDNA cloning, and sequence analysis the expression of membrane melatonin receptors in rat thymus and spleen. Results show, for the first time, that the melatonin receptor mRNA is expressed in both the thymus and spleen. Moreover, the melatonin receptor mRNA was expressed in all the lymphocyte subpopulations (CD4+,CD8+, double positive, double negative, and B cells) studied from the rat thymus. The Southern blot analysis with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 32 publications
5
96
0
1
Order By: Relevance
“…The results showed that positive cells located in germinal epithelium, extraovarian rete, follicular cells of the primordial follicle, primary follicle and oocytes in every follicle grade, and the staining intensity was strong. The presence of melatonin receptors in the ovary, mammary gland, testis, epididymis indicate that the direct melatonin actions on different levels of the reproductive system (Pang et al 1998;Pozo et al 1997). It indicates that there should be a part of melatonin effect on the ovary of ostrich chicks directly, besides the indirect effect through the hypothalamic-pituitary-gonadal axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that positive cells located in germinal epithelium, extraovarian rete, follicular cells of the primordial follicle, primary follicle and oocytes in every follicle grade, and the staining intensity was strong. The presence of melatonin receptors in the ovary, mammary gland, testis, epididymis indicate that the direct melatonin actions on different levels of the reproductive system (Pang et al 1998;Pozo et al 1997). It indicates that there should be a part of melatonin effect on the ovary of ostrich chicks directly, besides the indirect effect through the hypothalamic-pituitary-gonadal axis.…”
Section: Discussionmentioning
confidence: 99%
“…Ovary tissue samples from ostrich chicks were centrifuged 10 min at 3000 g in icecold lysis buffer [17 mM Tris-HCl pH 7.3 containing 0.144 M NH4Cl (Sigma)] to eliminate lymphocytes that express melatonin receptors (Pozo et al 1997). Tissues were homogenized using a Potter-Elvehjem homogenizer (20 strokes, on ice).…”
Section: Protein Isolation and Western Blot Analysismentioning
confidence: 99%
“…The evidence so far suggests that melatonin can influence immune cells through nuclear and membrane melatonin receptors. These receptors are found on macrophages, B cells, and T cells (Garcıá-Pergañeda et al 1999;Pozo et al 1997). Melatonin can modulate proliferation and cytokine secretion via these receptors on immune cells (García-Mauriño et al 2000;GarciaMaurino et al 1997).…”
Section: Role Of Melatonin In Immune Responses To Radiationmentioning
confidence: 99%
“…T cell apoptosis may also be blocked or partially blocked by zinc (359). In this context it is interesting to note the claim that the beneficial effects of melatonin supplementation or pineal grafting are associated with increased plasma zinc levels in old mice in the absence of exogenous zinc supplementation (532) (although melatonin may have direct effects on lymphocytes, which express melatonin receptors (533), ligation of which results in signal transduction and diacylglycerol production (534)). It is argued by Fabris et al that the common pathway of several life-extending endocrinological manipulations is in fact via zinc bioavailability (535).…”
Section: Vitamins and Minerals; Anti-oxidantsmentioning
confidence: 99%